Linguistic Features and Symbolic Communication in Àgídìgbo Music of the Yorùbá of Southwestern Nigeria - Adekola, Olaolu Emmanuel (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Music and language are inseparable, their relationship manifests in various contexts. Àgídìgbo music is one of the traditional music through which Yorùbá language is expressed and preserved because musicians usually deploy certain linguistic elements and communication devices in navigating their artistic creativity. Existing studies on music have not sufficiently examined how language, text and interpretation make sense in àgídìgbo music. This paper therefore, examined how language, text and interpretation in àgídìgbo music are used in express linguistic features, symbolic communication and nuances in African language. Ethnographic design was used and a purposive sampling technique was deployed to select three notable àgídìgbo exponents in Èrúwà (Oyo state), Abeòkúta (Ogun state) and Ìwó (Osun state) all in southwest Nigeria where àgídìgbo music performance is prevalent. Observation and In-depth interviews were employed as methods of data collection during social ceremonies of the key informants. Musical excerpts were recorded from live performances and data were subjected to content analyses. The findings revealed that the linguistic elements used in àgídìgbo music were proverbs and figures of speech such as hyperbole, metaphors, simile, fable, parables, repetition and digression clearly expressed communication device and nuances in Yorùbá language. The versatility and musical prowess of àgídìgbo musicians are not only measured by their virtuosity on the instrument but also by their ability to use the right and appropriate language elements such as òwe and other figures of speech in driving home their points thereby making àgídìgbo music to serve as repository for future generation.